Stigmasterol (Steroid) From Leaves of Solanum ferox L (Sour Eggplant) Plant - Hazimah; Fadhli, Haiyul; Fitriyah, Dina (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2023)
Solanum ferox L is a vegetable that is often used as a flavor in cooking that belongs to the Solanaceae family. Solanum ferox L contains terpenoids, steroids, flavonoids, alkaloids, and phenolic compounds. Solanum ferox has various bioactive compounds used as antirheumatic, antiasthma, antiviral, anticancer, and antibacterial. The aim of this study was to isolate and characterize the stigmasterol compound from the Solanum ferox plant. The compound was elucidated by UV, IR, and NMR spectroscopy and was named HSF. The HSF compound has the chemical formula C29H48O and the name is Stigmasterol.